2023
DOI: 10.1039/d3dt00955f
|View full text |Cite
|
Sign up to set email alerts
|

Methyldisulfide groups enable the direct connection of air-stable metal bis(terpyridine) complexes to gold surfaces

Abstract: We show that a new terpyridine ligand comprising a directly-connected methyldisulfide group (tpySSMe) can be used to prepare a modular series of metal bis(terpyidine) complexes, [M(tpySSMe)2](PF6)2 (M = Fe, Co,...

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(12 citation statements)
references
References 45 publications
3
9
0
Order By: Relevance
“…In a recent study, 20 we showed that the tpySS ligand can be utilized for the preparation of a new family of sulfur-functionalized redox-active MSS (M = Fe, Co, Zn) complexes. These compounds were found to be air-stable in solution for ≥7 days, in contrast to thiolfunctionalized analogues, 20,21 and capable of forming single-component SAMs on gold surfaces.…”
Section: Synthesis and Electrochemical Characterizationmentioning
confidence: 99%
See 4 more Smart Citations
“…In a recent study, 20 we showed that the tpySS ligand can be utilized for the preparation of a new family of sulfur-functionalized redox-active MSS (M = Fe, Co, Zn) complexes. These compounds were found to be air-stable in solution for ≥7 days, in contrast to thiolfunctionalized analogues, 20,21 and capable of forming single-component SAMs on gold surfaces.…”
Section: Synthesis and Electrochemical Characterizationmentioning
confidence: 99%
“…In a recent study, 20 we showed that the tpySS ligand can be utilized for the preparation of a new family of sulfur-functionalized redox-active MSS (M = Fe, Co, Zn) complexes. These compounds were found to be air-stable in solution for ≥7 days, in contrast to thiolfunctionalized analogues, 20,21 and capable of forming single-component SAMs on gold surfaces. Here we report that analogous RuSS-1 and RuSS complexes may also be synthesized from tpySS and RuCl2(DMSO)(tpy) following the method of Ziessel et al, 29 using reaction temperatures that do not exceed 60℃.…”
Section: Synthesis and Electrochemical Characterizationmentioning
confidence: 99%
See 3 more Smart Citations